2021
DOI: 10.1021/acs.macromol.1c01805
|View full text |Cite
|
Sign up to set email alerts
|

Surface Segregation in Athermal Polymer Blends Due to Conformational Asymmetry

Abstract: Monte Carlo simulations are used to investigate the surfaces of athermal blends of stiff and flexible polymers as the bending modulus of the stiff polymers, κ, is increased from zero to the point where the bulk undergoes an isotropic−nematic transition. For hard walls characteristic of polymer/solid surfaces, the flexible polymers generally segregate to the surface. However, just prior to the bulk transition, a surface transition occurs where a thin nematic layer rich in stiff polymers forms next to the wall. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(23 citation statements)
references
References 39 publications
9
13
1
Order By: Relevance
“…On the other hand, molecular dynamics (MD) simulations on diblock copolymer melts by Nikoubashman et al 19 reported a preference for the component with the shorter statistical segment length. Most recently, we performed MC simulations of flexible and stiff polymers 20 polymer, quantitatively consistent with the SCFT calculations of Wu et al 15 Despite their diametrically opposing conclusions, the only meaningful difference between the simulations of Kumar and coworkers 16,17 and our previous ones 20 is that they are based on off-lattice and lattice models, respectively. It is a common practice to restrict the monomers of large and relatively flexible polymers to a lattice so as to increase the computational efficiency of simulations, with the expectation that the artificial lattice will not alter the qualitative behavior.…”
Section: ■ Introductionsupporting
confidence: 59%
See 4 more Smart Citations
“…On the other hand, molecular dynamics (MD) simulations on diblock copolymer melts by Nikoubashman et al 19 reported a preference for the component with the shorter statistical segment length. Most recently, we performed MC simulations of flexible and stiff polymers 20 polymer, quantitatively consistent with the SCFT calculations of Wu et al 15 Despite their diametrically opposing conclusions, the only meaningful difference between the simulations of Kumar and coworkers 16,17 and our previous ones 20 is that they are based on off-lattice and lattice models, respectively. It is a common practice to restrict the monomers of large and relatively flexible polymers to a lattice so as to increase the computational efficiency of simulations, with the expectation that the artificial lattice will not alter the qualitative behavior.…”
Section: ■ Introductionsupporting
confidence: 59%
“…The differences are most severe for the larger polymers, but they still remain significant even for their shortest N = 10 polymer. The inconsistency is readily explained by a lack of equilibration as initially suspected 20 as well as a lack of statistics. We performed many orders of magnitude more equilibration and several orders of magnitude more statistics.…”
Section: ■ Discussionmentioning
confidence: 99%
See 3 more Smart Citations